2020
DOI: 10.14716/ijtech.v11i3.3750
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Supply Chain for a Single Vendor and Multiple Buyers and Products with Crashing Lead Time

Abstract: In this study, an integrated inventory model was developed among one vendor, multi buyers, and multi products. The total inventory cost to be minimized in this model is a combination of the vendor's and the buyers' total inventory costs. The total vendor inventory costs consist of setup costs and holding costs and the total inventory cost of the buyer consists of ordering costs, holding costs, stockout costs, and crashing lead time costs where the crashing lead time cost is approximated with an exponential fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In fact, to maintain business continuity, currently companies have maximized the use of information technology (IT) based on the Internet of Things (IoT) to gain a competitive advantage through product offerings and help the business world to continue to innovate and facilitate online access [10,11]. Integrated supply chain collaboration for business performance based on strategic planning work models and operational multi-criteria analysis can use the Analytic Network Process method in comprehensive decision making and use ANP as supply chain collaboration for e-business performance-based frameworks to bring organizations to achieve competitive advantage [12][13][14][15][16]. This has been done by [17] in strengthening palm oil supply chain institutions, it is supported by associations, government, financial institutions and key actors to ensure the smooth running of the supply chain.…”
Section: Hiyung Wonderfull Wetland Lambung Mangkurat University (Hw2 ...mentioning
confidence: 99%
“…In fact, to maintain business continuity, currently companies have maximized the use of information technology (IT) based on the Internet of Things (IoT) to gain a competitive advantage through product offerings and help the business world to continue to innovate and facilitate online access [10,11]. Integrated supply chain collaboration for business performance based on strategic planning work models and operational multi-criteria analysis can use the Analytic Network Process method in comprehensive decision making and use ANP as supply chain collaboration for e-business performance-based frameworks to bring organizations to achieve competitive advantage [12][13][14][15][16]. This has been done by [17] in strengthening palm oil supply chain institutions, it is supported by associations, government, financial institutions and key actors to ensure the smooth running of the supply chain.…”
Section: Hiyung Wonderfull Wetland Lambung Mangkurat University (Hw2 ...mentioning
confidence: 99%
“…Chan et al (2018) showed that the synchronization of the buyers ordering cycle length and vendor production cycle length gives better result than both decentralised policy and common cycle policy when stock out condition permitted under stochastic demand. Aritonang et al (2020) proposed a mathematical model that minimizes the total cost for a SVMB supply chain system, where each vendor shipment is shared between multiple buyers that are experiencing stochastic demand in sales and have adjustable lead time that ensures all buyers receive equal numbers of delivery shipments. Vandana and Sana (2020) introduced ameliorating items like livestock, and the accumulated inventory is assumed to depend on the procreation and deterioration (birth) rate.…”
Section: Stochastic Modelsmentioning
confidence: 99%
“…Income is determined by the money obtained by selling the product with the deduction of tax and expenses. We predict sales of the product using an integrated supply chain model (Aritonang et al, 2020). Cash flow can be calculated by subtracting outgoings from the income.…”
Section: System Performance Benchmarkmentioning
confidence: 99%